1982
DOI: 10.1085/jgp.79.6.997
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cross-bridge kinetics on apparent Ca2+ sensitivity.

Abstract: Three different ways of shifting the pCa/tension curve on the pCa axis have been studied and related to changes in the rate constants of the crossbridge cycle. The curve midpoint shifts to higher pCa's wheel the substrate (Mg-ATP) is reduced from 5 to 0.25 mM, when the phosphate concentration is reduced from 7.5 mM to 0, and when the ionic strength is reduced from 0.200 to 0.120 . The Hill coefficients of the pCa/tension curve in our standard saline (5 mM substrate, 5 mM free ATP, 7.5 mM phosphate, ionic stren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
43
4

Year Published

1986
1986
2002
2002

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(57 citation statements)
references
References 49 publications
10
43
4
Order By: Relevance
“…1-3). Similar inhibitory effects of Pi have been observed with glycerinated or skinned muscle from pig hearts (Herzig & Riiegg, 1977;Herzig et al 1981) and with skinned rabbit psoas fibres (Brandt et al 1982), though it is not clear whether the Ca2+ and Mg2+ concentrations were kept constant in these earlier studies. More recently there have been preliminary reports of similar effects in skinned fibres from frog (Godt, Fender & Nosek, 1984) and fish (Johnston & Altringham, 1985).…”
Section: Influence Of Pi On the Force-[ca2+] Relationshipsupporting
confidence: 53%
See 1 more Smart Citation
“…1-3). Similar inhibitory effects of Pi have been observed with glycerinated or skinned muscle from pig hearts (Herzig & Riiegg, 1977;Herzig et al 1981) and with skinned rabbit psoas fibres (Brandt et al 1982), though it is not clear whether the Ca2+ and Mg2+ concentrations were kept constant in these earlier studies. More recently there have been preliminary reports of similar effects in skinned fibres from frog (Godt, Fender & Nosek, 1984) and fish (Johnston & Altringham, 1985).…”
Section: Influence Of Pi On the Force-[ca2+] Relationshipsupporting
confidence: 53%
“…More recently Brandt, Cox, Kawai & Robinson (1982) reported that, in skinned skeletal fibres, Pi reduced not only the maximum force but also the Ca2+ sensitivity of the myofibrils (i.e. increased the [Ca2+] required for a given degree of myofibrillar activation).…”
Section: Introductionmentioning
confidence: 99%
“…This will increase the cycling rate of the crossbridges and could result in a rightward shift of the force-[Ca2"] relation. 25 According to the scheme, the combined effect of BDM on both sites will result in the observed experimental effect, an increase in [Ca2+]50% and a reduction in Fmax* In this scheme, we would expect the rate of ATP hydrolysis to be decreased by BDM, which has been shown to be the case in previous reports. '1043…”
Section: Velocity Of Unloaded Shorteningmentioning
confidence: 73%
“…Tension was normalized to the maximum tension at pCa 4.66 before plotting. The data were fitted to the Hill equation (eqn (1); Brandt et al 1980Brandt et al , 1982 to determine the cooperativity (n) and the Ca 2+ dissociation constant (K):…”
Section: Pca-tension Measurementsmentioning
confidence: 99%